Is the finding of endometrial hyperplasia or corporal polyp an mandatory indication for biopsy? - Vinklerová, P; Felsinger, M; Frydová, S; Ovesná, P; Hausnerová, J; Weinberger, V (Ceska gynekologie, 2020)
OBJECTIVE: The aim of our study was to analyze a group of patients referred for endometrial biopsy. To evaluate the ultrasound finding of hyperplasia/polyp, the symptomatology of patients related to the result of definitive histology, to determine the severity of individual variables in connection with the detection of precancerosis/cancer. Due to the complexity of information identify women who are suitable for conservative approach. DESIGN: Unicentric retrospective observational study. SETTING: Department of Obstetrics and Gynecology, Masaryk University, University Hospital Brno. METHODS: All patients over 50 years who underwent surgical endometrial biopsy at our department in the period of 2017-2018 (n = 754) were included. We were interested in reasons of indication, the age of patients at the time of the procedure and at the menopause, the presence of risk factors for development precancerosis/cancer (hypertension, diabetes mellitus, using of tamoxifen), number of deliveries and pregnancies, symptomatology, the description of ultrasound scans, the result of histology examination, peroperative and postoperative complications. RESULTS: Perimenopause - the median of endometrial thickness in both benign and malignant histology was 8 mm (p = 0.448), the median of the largest polyp dimension was 18 mm. All patients with precancerosis/malignancy were symptomatic with irregular/excessive bleeding, no carcinoma was found in polyp. Postmenopause - the median of endometrial thickness in benign histology was 7 mm versus 16 mm in precancerosis/malignancy (p < 0.001), the median of the largest polyp dimension was the same in both histologies (13 mm, p = 0.274). The risk of malignancy was more than threefold in bleeding versus asymptomatic patients with both hyperplasia and polyp (OR 3.39, 3.79). In asymptomatic patients the risk of cancer was similar for selected cut-offs (5, 8 and 12 mm), statistically significant only for 12 mm (OR 3.54), while in symptomatic patients the risk was high for all cut-offs, however with wide confidence intervals, statistically significant for cut-offs of 8 mm (minimum 3.58) and 12 mm (minimum 4.94). CONCLUSION: We have shown that symptomatology is a strong risk factor for the presence of precancerosis/malignancy in patients with endometrial hyperplasia or polyp. The thickness of the endometrium or polyp size in asymptomatic patients does not play a major role. Ultrasound alone does not have sufficient accuracy for detection or even screening of endometrial cancer. We recommend a conservative procedure, monitoring changes in the ultrasound scan and symptomatology of the patient over time.
Keywords: nádory endometria; endometrial hyperplasia; Female; polypy; ultrasonografie; ženské pohlaví; biopsie; endometrium; Uterine Hemorrhage; hyperplazie endometria; lidé; hysteroskopie; těhotenství; Ultrasonography; hysteroscopy; Endometrial Hyperplasia; retrospektivní studie; Polyps; endometrial cancer; Biopsy; děložní krvácení; Endometrium; Hysteroscopy; postmenopausal bleeding; Endometrial Neoplasms; curettage; Pregnancy; polyp; Retrospective Studies; Humans